2004
DOI: 10.1063/1.1790067
|View full text |Cite
|
Sign up to set email alerts
|

β - δ phase transition during dropweight impact on cyclotetramethylene-tetranitroamine

Abstract: The secondary explosive cyclotetramethylene-tetranitroamine (HMX) exists in a variety of crystal structures; the most widely used being the β-phase which is stable at room temperature and pressure. On heating, a more impact sensitive form (δ phase) is produced. The nonlinear optical technique of second harmonic generation (SHG) can be used as a probe of phase since δ-phase HMX generates a second harmonic at 532nm when 1064nm laser light is incident upon it. We present high-speed photography of SHG in HMX sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…The δ phase is reported to be a more impact sensitive form than the β phase 23. The phase transition with drop‐weight impact on HMX 24 has been investigated at room temperature with second harmonic generation (SHG) 23. However, the in situ phase transition by impact test has not been previously reported.…”
Section: Resultsmentioning
confidence: 99%
“…The δ phase is reported to be a more impact sensitive form than the β phase 23. The phase transition with drop‐weight impact on HMX 24 has been investigated at room temperature with second harmonic generation (SHG) 23. However, the in situ phase transition by impact test has not been previously reported.…”
Section: Resultsmentioning
confidence: 99%
“…The purpose of the present study is to enable mechanical responses and violent burning to be visualized using high-speed photography rather than to rank explosives according to sensitivity. The nonlinear optical technique of second harmonic generation has been used as a probe of d-phase HMX during drop-weight impact when laser light is incident upon it (Czerski et al, 2004). These researchers also investigated the occurrence conditions of b-d phase change during impact, which showed that b-d phase change and ignition appear to be intimately related (Czerski et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…1 3 The detonation performance and specifically the sensitivity of HMX not only have a relationship with the morphology 4 7 of the HMX crystals, but also depend on the defects 8 present in the crystals and the crystal phase. 9 The attachment stability of growth units (HMX molecules) on each surface of the crystal affects the crystal morphology. In addition, the crystal morphology is also connected with the physical and chemical conditions during growth.…”
Section: Introductionmentioning
confidence: 99%